THE INFLUENCE OF DIGITAL MARKETING, PRODUCT QUALITY, AND PRICE ON THE DECISIONS TO PURCHASE AT NIM SHOP AND ITS IMPACT ON THE SATISFACTION OF CUSTOMER - Farreza; Wahyuningsih; Asngadi (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This research aims to determine the influence of Digital Marketing, Product Quality, and Price on Purchasing Decisions with Consumer Satisfaction as an Intervening Variable. The population was the people of Palu who shop at Nim Shop. Type of the research was explanatory research using a quantitative approach with a total sample of 100 respondents. The data analysis technique used Partial Least Square (PLS) with the sampling technique applied the Structural Equation Modeling (SEM) method. The results of the research show that digital marketing has a significant influence on purchasing decisions; Product quality has a significant influence on purchasing decisions; Prices have a significant influence on purchasing decisions; Purchase decisions have a significant influence on purchase satisfaction; Digital marketing has a significant influence on purchase satisfaction; Product quality has a significant influence on purchase satisfaction; Price has a significant influence on purchase satisfaction; There is no direct influence of digital marketing on purchase satisfaction through purchasing decisions; The direct influence of product quality on purchase satisfaction through purchasing decisions; The direct influence of price on purchase satisfaction through purchasing decisions.